(3TQM QSGdI GdhVYs - (3GdMSf Hf CMeO GdLdGds ((3eMeO Hf ESeGYjd GdCejQ s)
(3ChdgG (B:s
(3GdMeO ddg hGVY GdejRGf hQGaY GdEfSGf HGddSGf hHYO aEfi deG EWdYJ Ydi GdQSGdI GdhVYjI ddEeGe GdeMbb YVO Gdedg hGdOjf s
(3BNQgG (B:s
(3hJJe Hg GdOdGg eTJedkG HGdJeGe Jee Gddg dfG hdc eG fQLhg ef aVdg GdYeje hLYd CYeGdfG eJhLgI Edi hLgI GdcQje EfJgJ GdQSGdI hTQMgG s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH(B4s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3Ydi UaMI GdYfhGf GdeNWhW ehba Ydi PQjI SjOi GdMSjf Hf Ydis
(3hHChdg fbhd eNJdaI HghGeTgG JYdjbGJ s
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
Keywords: (3GdeLGejYs